EFFICACY OF VARIOUS BIOFILTER MEDIA IN A CLOSED RECIRCULATING SYSTEM FOR LARVICULTURE OF MACROBRACHIUM ROSENBERGII - Chandrakant M.H; Reddy A.K.; Mal B.C; Verma A.K. (Journal of Indian Fisheries Association, 2018)
Efficacy of 4 different biofilter media viz. plastic bio-balls, charcoal, zeolite stones and molluscan shells was evaluated in a closed recirculating system for larviculture of Macrobrachium rosenbergii. The larvae of M. rosenbergii were reared in 3 cycles using natural and synthetic seawaters. The larvae were stocked @ 100 per liter and reared till 9096 larvae metamorphosed into post-larvae (PL). The results indicate that all biofilters are capable of maintaining water quality parameters within the optimum range. Concentration of ammonia (NH4+-N), nitrite (NO2 -N), nitrate (NO3 -N and phosphate (PO4,-P) were significantly (P